2011
DOI: 10.1504/ijte.2011.043723
|View full text |Cite
|
Sign up to set email alerts
|

Research institutes and R&D subsidies: Taiwan's national innovation system and policy experiences

Abstract: In Taiwan's national innovation system, the Government-Sponsored Research Institutes (GSRIs) facilitate technology assimilation and/or transfer and cooperative R&D promotion in support of firms, and also act as a policy assistant. Drawing on the dataset of the "Local Industry Innovation Engine Program", the study quantitatively compares various types of the R&D alliances initiated by GSRIs and the types of R&D grants they received. Based on the empirical evidence, the study argues that there are significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Of the two countries, only Taiwan conducted a formal study on the impact of its tax incentives. Tax credits for encouraging R&D, training, and green energy induced further R&D investment, with significant positive net effects on tax revenue (Liu and Wen 2011). In the case of Thailand, though one cannot claim direct causation, the results of community innovation surveys illustrate that innovating firms take advantage of R&D tax incentives more frequently than non-innovating firms.…”
Section: Tax Incentivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the two countries, only Taiwan conducted a formal study on the impact of its tax incentives. Tax credits for encouraging R&D, training, and green energy induced further R&D investment, with significant positive net effects on tax revenue (Liu and Wen 2011). In the case of Thailand, though one cannot claim direct causation, the results of community innovation surveys illustrate that innovating firms take advantage of R&D tax incentives more frequently than non-innovating firms.…”
Section: Tax Incentivesmentioning
confidence: 99%
“…Results of the LPD program were quite impressive: $1 TWD of grant induced an additional investment of approximately $10 TWD for R&D, $21 TWD investment for production, and $42 TWD for sales. On average, one project generated 3.7 patents and 2.9 derivative products (Liu and Wen 2011).…”
Section: Grantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Etzkowitz [51] claimed that government R&D subsidies are an important policy instrument to remove the boundary between universities and firms. Empirically, Liu and Wen [52] studied firms that participated in the Taiwanese government subsidy program and proved that government subsidies had vitalized technology transfer from research organizations and R&D alliances. Greco, Grimaldi, and Cricelli [53] in their study of 43,230 European firms demonstrated that public R&D subsidies increased cooperation with external organizations, which is open innovation, at local, national, and European level.…”
Section: Behavior Additionality: Strategic Alliance and External Finamentioning
confidence: 99%
“…By listing in the MAI, firms gain prestige, which is quite helpful in terms of mar- Source Constructed by authors tiums). However, the status of MOEA has been weaker since the abolition of martial law in the late 1980s and as a result of recently rising public financial deficit problems (Liu and Wen 2011). The situation is very different in Thailand, where the Ministry of Science and Technology had not been considered as an 'economic' ministry until the present government took power in 2014.…”
Section: Capital Market Fundingmentioning
confidence: 99%